2002
DOI: 10.1200/jco.20.3.776
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in High-Grade Osteosarcoma of the Extremities or Trunk: An Analysis of 1,702 Patients Treated on Neoadjuvant Cooperative Osteosarcoma Study Group Protocols

Abstract: Tumor site and size, primary metastases, response to chemotherapy, and surgical remission are of independent prognostic value in osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

93
1,401
10
63

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,465 publications
(1,567 citation statements)
references
References 57 publications
93
1,401
10
63
Order By: Relevance
“…The theory that good histologic response correlates with improved prognosis has been supported in the literature [9,42]. The use of serial arteriography in our study had a 92.5% rate of accuracy and 100% sensitivity in predicting good tumor response (greater than 90%).…”
Section: Discussionsupporting
confidence: 66%
“…The theory that good histologic response correlates with improved prognosis has been supported in the literature [9,42]. The use of serial arteriography in our study had a 92.5% rate of accuracy and 100% sensitivity in predicting good tumor response (greater than 90%).…”
Section: Discussionsupporting
confidence: 66%
“…Adverse survival in childhood acute lymphoblastic leukemia (ALL) is associated with several single nucleotide polymorphisms (SNPs), including MTHFR c.677C>T p.Ala 222 Val, also known to enhance methotrexate toxicity in both ALL and solid tumors. 2,3,6,[13][14][15][16] In osteosarcoma, MTHFR c.677C>T p.Ala 222 Val increased hematological toxicity but did not influence survival. 17 Cisplatin and doxorubicin form helix-distorting DNA adducts resulting in strand breakage and inhibition of replication.…”
Section: Introductionmentioning
confidence: 94%
“…However, approximately 40% patients show a poor response to chemotherapy, with inferior 5-year survival of 45% to 55%. 2 Furthermore, 60% of bone tumor survivors experience severe or disabling chronic health conditions 30 years from diagnosis. 3 Little is known about MAP chemotherapy pharmacogenomics, but information gained from the use of these agents in other malignancies provides insight into potentially critical pathway components.…”
Section: Introductionmentioning
confidence: 99%
“…Talac et al 14 described in their study of spinal sarcomas that residual tumor at the surgical margin, and resection in a piecemeal fashion, resulted in a high recurrence rate that was associated with early mortality. Similarly, a recent review of 1702 patients with high-grade osteosarcoma 5 indicated that failure to achieve a surgical remission of osteosarcoma was associated with increased age, axial site, long history, delayed start of therapy, intralesional surgical resection, and poor response to chemotherapy. However, Gore et al 15 reported a case with long-term survival after intralesional resection of thoracic spine osteosarcoma with multidisciplinary, multimodal approach, using aggressive chemoradiotherapy with surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Osteosarcoma is a malignant bone tumor that frequently affects patients in their second and third decades of life, however, it is reported there exists two peaks in the incidence of osteosarcoma, one is in the second decade and another in the seventh decade of life. 7 Huvos 8 reported three cases of osteosarcoma of the spine among 117 patients with osteosarcoma older than 60 years.…”
Section: Introductionmentioning
confidence: 99%